Divine Illocutions in Psalm 137: A Critique of Nicholas Wolterstorff’s ‘Second Hermeneutic’ - Barker, Kit (2009)
Recent years have witnessed renewed interest in understanding Scripture as divine communication, a move which reconnects the academy with ecclesiological concerns. Those involved in theological hermeneutics have drawn upon advances in a wide range of disciplines in order to develop and defend their methodologies. From the fields of communication theory and pragmatics, speech act theory has been proffered by some as providing insightful analysis of the anatomy of communication and, in particular, authorial intention. Nicholas Wolterstorff’s, Divine Discourse: Philosophical Reflections on the Claim that God Speaks is representative of such works. Drawing heavily upon speech act theory, Wolterstorff defends a model of interpretation that prioritises authorial intention. Furthermore, Wolterstorff’s conviction that Scripture is both human and divine discourse leads him to a two-stage hermeneutic. This paper will offer an explanation and critique of Wolterstorff’s move from the first to the second hermeneutic in his interpretation of Psalm 137. It will conclude that while Wolterstorff’s method does account for the divine intention in part, it ultimately suffers from both a limited connection to speech act theory and a failure to appreciate the nature of communication at higher (especially generic) levels. In addressing these methodological deficiencies, the paper will present Psalm 137 as an authoritative canonical text by clarifying how it continues to function as divine discourse.
Keywords: authorial intention; Speech Act Theory; wolterstorff; Psalms; Hermeneutics; Old Testament